Prognosis of Patient With Resorbable Plates and Screws Under the Incision Site. Issue 7 (October 2020) - Shin, Jin Yong; Roh, Si-Gyun; Chang, Suk Choo; Lee, Nae-Ho
Abstract : Abstract: Various resorbable plates and screws were used for facial bone fractures because of several strengths. However, there are few studies on their clinical course and long-term follow-up concerning their degradation and resorption time. The authors present rare case of long term follow-up of resorbable plates and screws under the incision site.